Characterization of nucleoside-diphosphate kinase-associated guanine nucleotide-binding proteins from HeLa S3 cells - Ohtsuki, Kenzo; Ikeuchi, Tohru; Yokoyama, Minehiko (Biochimica et Biophysica Acta (BBA) - General Subjects, 1986)
Nucleoside-diphosphate (NDP) kinase-associated [ α- 32P]GTP-incorporating proteins from HeLa S3 cells have been biochemically characterized. Two distinct NDP-kinases (F-I and F-II) had been partially purified from HeLa S3 cells by Sephacryl S-300 gel filtration and DEAE-cellulose column chromatography. The [ α- 32P]GTP-incorporating proteins (approx. M r 20 000) could be separated from NDP-kinases (approx. M r 80 000) by 5–25% glycerol density-gradient centrifugation analysis after treatment with 7 M urea in the presence of 1 mM EDTA. [ α- 32P]GPT incorporation into these two proteins (G1 and G2) from NDP-kinases required 5 mM Mg 2+ and was highly inhibited by either GDP or GTP analogues, such as guanylyl imidodiphosphate and guanylyl methylenediphosphate. [ 3H]GDP, but not other nucleoside 5′-diphosphates, was also bound to these two proteins in the presence of Mg 2+ (5 mM). Moreover, incubation of [ α- 32P]GPT with either G1 or G2 in the presence of Mg 2+ (5 mM) resulted in the formation of [ 32P]GDP and P i. The data presented here indicated that (a) the guanine nucleotide-binding activity, (b) the GTPase activity, and (c) the molecular weight (approx. M r 20 000) of NDP kinase-associated proteins from HeLa S3 cells are similar to those reported for ras oncogene products (p21 proteins).